Active near-infrared wavefront engineering employing geometric phase metasurfaces combined with phase-change materials. (5th May 2021) - Fan, Junxing; Lei, Ting; Yuan, Xiaocong
Abstract: In recent years, with the remarkable development of micro–nano technology, phase change materials (PCMs) with superior tunable and nonvolatile functionality are integrated into metasurfaces, which has aroused huge interests among scientific communities. However, the imaginary part of refractive index of PCMs in the crystalline phase is large in the near-infrared region (NIR), leading to the strong absorption of device and limiting the development of the PCMs in the NIR. Here, we propose and investigate the hybrid metasurface with asymmetric double-split rings. We use PCM and silica (SiO2 ) as the composite dielectric layer, which can efficiently reduce the impact of the high imaginary part of the refractive index PCM in the crystalline phase. Moreover, metasurfaces with two types can obtain two different resonances. Furthermore, by inducing the phase change of the PCM, we can move the short-wavelength resonance peak to the position of another long-wavelength resonance peak. Meanwhile, we can add two sets of different phases to two different types of metasurfaces. Thus, the active metasurface based on the PCM can be used to achieve the active wavefront in the NIR. Hence, the proposed metasurface based on the PCM can be applied in tunable beam switching, reconfigurable holography, and other reconfigurable optical components in the NIR.